Indonesian Government Intervention in the Management of Indonesian Migrant Workers’ Remittances: Is It Constitu- tionally Justified? - Ayuningtyas, Annisa; Yuniza, Mailinda Eka (Society for South-East Asian Studies (SEAS), 2022)
The latest law on the protection of Indonesian Migrant Workers (IMWs), Law Number 18 of 2017 (Law 18/2017), obliges the Indonesian government to conduct economic pro- tection through remittance management by involving certain institutions. Nonetheless, there is a lack of clarity about how this intervention would occur. The private nature of migrant workers’ remittances leads to the question of constitutional justification essential for the government’s authority to intervene – particularly in Indonesia as a constitutional state in the form of a welfare state – besides skepticism concerning the applicability of the norm. This paper emphasizes the constitutional silence with regard to state intervention in human resources allocation, as it makes the deployment of Indonesian workers abroad constitutionally groundless. Consequently, the discretion infiltrates the remittance, a component of national income that is essentially a private transfer in which the manage- ment should be fully controlled by the families. Through review of the scientific literature and legal document analysis, this research found that the inclusion of a state intervention provision on human resources into the 1945 Constitution is still required.